Changes in shape and composition of sea-salt particles upon aging in an urban atmosphere. (January 2015) - Adachi, Kouji; Buseck, Peter R.
Abstract: Sea salt is one of the most abundant types of natural aerosol particles and significantly influences local and global climate. It is an important constituent of samples collected between June 10 and 15 in the Los Angeles area during the 2010 CalNex campaign. The sea-salt particles reacted with other species in the atmosphere and became Na-bearing aerosol (NaA) particles. Using transmission electron microscopy, we found that Na occurred in almost half of all analyzed particles (∼3500), although commonly only in minor amounts. Almost all the NaA particles contained S but not Cl, suggesting that Cl was depleted through particle formation to sulfate, nitrate, or both in the urban atmosphere. We observed both rounded and euhedral NaA particles. The rounded ones consisted mainly of aged sea salt (>12 h) that had reacted extensively with sulfate, whereas the euhedral ones occurred in samples from relatively fresh marine air. The shapes and compositions of NaA particles changed within 3 h in the urban atmosphere. Moreover, our calculations indicate that light scattering from NaA particles depends on their shapes (e.g., roughly spherical, flat, or elongated). These compositions and shapes affect hygroscopicities and light scattering, respectively, both of which influence their climate effects. Highlights: Na occurs in almost half of the analyzed particles. Sea-salt particles change compositions within several hours after emission. Sea-salt particles change their effects on climate as they age in urban air.